2019
DOI: 10.1002/ehf2.12551
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in cardio‐oncology: a report from the ‘Heart Failure Association 2019 and World Congress on Acute Heart Failure 2019’

Abstract: While anti-cancer therapies, including chemotherapy, immunotherapy, radiotherapy, and targeted therapy, are constantly advancing, cardiovascular toxicity has become a major challenge for cardiologists and oncologists. This has led to an increasing demand of cardio-oncology units in Europe and a growing interest of clinicians and researchers. The Heart Failure 2019 meeting of the Heart Failure Association of the European Society of Cardiology in Athens has therefore created a scientific programme that included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 97 publications
(147 reference statements)
0
20
0
Order By: Relevance
“…Explanations for this phenomenon are an increased awareness of cardiotoxicity in patients receiving chemotherapy, a prolonged survival for young cancer patients exposing them to long-term cardiotoxicity risks, and an explosive growth of alternative anticancer drugs based on small molecules (e.g., tyrosine kinase inhibitors, proteasome inhibitors, etc.) [ 3 , 4 ]. There is increased awareness that cardiotoxicity might even lead to premature morbidity and death in young cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Explanations for this phenomenon are an increased awareness of cardiotoxicity in patients receiving chemotherapy, a prolonged survival for young cancer patients exposing them to long-term cardiotoxicity risks, and an explosive growth of alternative anticancer drugs based on small molecules (e.g., tyrosine kinase inhibitors, proteasome inhibitors, etc.) [ 3 , 4 ]. There is increased awareness that cardiotoxicity might even lead to premature morbidity and death in young cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…However, these agents are associated with side effects, cardiotoxicity among them, which limits treatment options and contributes to morbidity and mortality in these patients [1][2][3][4]. Therefore, there is a critical need to understand the pathophysiological mechanisms taking place in the myocardium of patients undergoing cancer chemotherapy before irreversible cardiac damage occurs [5].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, cardiotoxicity due to breast cancer treatment, particularly anthracycline-based cancer chemotherapy (ACC), has been attributed to cardiomyocyte damage and death, with amino-terminal pro-brain natriuretic peptide (NT-proBNP) and high-sensitivity troponins (hs-Tn) as the most commonly used biomarkers to detect cardiac damage in these patients [5,6]. However, it has been suggested that myocardial interstitial brosis (MIF) is an additional important mechanism contributing to left ventricular dysfunction (LVD) and adverse clinical evolution in ACC-treated patients [6,7], as well as in patients treated with other oncologic drugs such as cyclophosphamide, taxane agents and anti-HER2 therapies [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Therefore, there is a critical need to understand the pathophysiological mechanisms taking place in the myocardium of patients undergoing cancer chemotherapy before irreversible cardiac damage occurs. 5 Traditionally, cardiotoxicity due to breast cancer treatment, particularly anthracycline-based cancer chemotherapy (ACC), has been attributed to cardiomyocyte damage and death, with amino-terminal pro-brain natriuretic peptide (NT-proBNP) and high-sensitivity troponins (hs-Tn) as the most commonly used biomarkers to detect cardiac damage in these patients. 5,6 However, it has been suggested that myocardial interstitial brosis (MIF) is an additional important mechanism contributing to left ventricular dysfunction (LVD) and adverse clinical evolution in ACC-treated patients, 6,7 as well as in patients treated with other oncologic drugs such as cyclophosphamide, taxane agents and anti-HER2 therapies.…”
Section: Introductionmentioning
confidence: 99%
“…5 Traditionally, cardiotoxicity due to breast cancer treatment, particularly anthracycline-based cancer chemotherapy (ACC), has been attributed to cardiomyocyte damage and death, with amino-terminal pro-brain natriuretic peptide (NT-proBNP) and high-sensitivity troponins (hs-Tn) as the most commonly used biomarkers to detect cardiac damage in these patients. 5,6 However, it has been suggested that myocardial interstitial brosis (MIF) is an additional important mechanism contributing to left ventricular dysfunction (LVD) and adverse clinical evolution in ACC-treated patients, 6,7 as well as in patients treated with other oncologic drugs such as cyclophosphamide, taxane agents and anti-HER2 therapies. [8][9][10][11][12][13][14] As cumulative evidence suggest that the detrimental impact of MIF on LV function is related to both an excess in collagen type-I ber cross-linking and deposition, 15 these characteristics of the collagen ber should be evaluated in the myocardium of patients receiving ACC.…”
Section: Introductionmentioning
confidence: 99%